STRATEGIC DEBT: A CONCEPTUAL FRAMEWORK AND DIAGNOSTIC INSTRUMENT FOR STRATEGY-FOUNDATION GAPS IN VENTURE-BACKED EARLY MOVERS - Muhammad Harland; Asep Darmansyah (RADJA PUBLIKA, 2026)
Early movers that create an uncontested market space frequently deteriorate financially soon after competitors enter, and the deterioration is commonly diagnosed as a financial or execution failure. This article proposes an alternative explanation and the instrument to test it. Drawing on Porter's account of strategy as trade-off, Rumelt's hallmarks of bad strategy, Kim and Mauborgne's blue ocean framework, agency theory, and the technical-debt metaphor from software engineering, the article develops the construct of strategic debt: the deferred cost of strategy fundamentals not built while an uncontested market makes them appear unnecessary, and which is priced, with interest, through identifiable profit-and-loss mechanisms once competition arrives. The article makes three contributions. First, it specifies the construct, its accrual conditions, its pricing trigger, and its boundary conditions, arguing that the invisibility of the cost during the uncontested phase is not a managerial oversight but a structural property of the phase itself. Second, it derives a six-category taxonomy of strategy-foundation gaps covering external measurement, target logic, investment gating, portfolio discipline, channel economics, and contra-revenue governance, each anchored to an established strategy principle. Third, it operationalizes the construct as the strategic gap ledger, a diagnostic instrument that traces each gap through a four-link causal chain from gap to observable managerial behavior to profit-and-loss mechanism to quantified impact, rendering an otherwise abstract deficit measurable in monetary terms. A stylized illustration demonstrates the instrument's application, and six falsifiable propositions are advanced for empirical testing. The framework is conceptual and awaits validation; its practical implication is that the strategy foundation must be built during the uncontested phase, precisely when it appears least necessary, because its absence is priced only after the transition, when remediation costs have multiplied.